APPLICATION OF GUIDED QUESTION AND ANSWER METHOD TO IMPROVE PAI LEARNING ACHIEVEMENT OF STATE JUNIOR HIGH SCHOOL 1 SEI RAMPAH - Hadi Widodo (UIN Sumatera Utara Medan, 2020)
This research is aimed to reveal the results of learning activities through classroom action research that have been applied for three cycles which each cycle consisted of planning, action, observation, and reflection. This research applied Guided Question and Answer to increase PAI learning achievement at State Junior High School. Based on all the discussions and analyzes that have been carried out, it can be concluded that there is the improvement in every cycle for the PAI students' achievement by using guided question and answer. By applying this method, the critical thinking of the students is improved as well. Moreover, learning achievement with the quidded question and answer method has positive impact on improving student learning achievement which is marked by increased student learning completeness in each cycle. In cycle I, the percentage of students learning minimal completeness criteria is 35.56%. In cycle II, minimal completeness criteria is 49.22%. Last, in cycle III, minimal completeness criteria is 85.20%. Thus, the application of the guided question and answer method of learning has a positive effect.